2016
DOI: 10.5603/gp.2016.0027
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic salpingectomy for prevention of sporadic ovarian cancer — a jump from basic science to clinical practice?

Abstract: Ovarian cancer is the most malignant and aggressive gynecological cancer. Due to nonspecific symptoms in the early stage and a lack of effective screening methods, it is typically diagnosed at an advanced stage. The high-grade serous cancer (HGSC) represents 75% of all ovarian cancers and accounts for the majority of deaths. Contemporary thought suggests that precursor lesions of HGSC originate in the fallopian tube. The presumed precursor tubal lesion, localized at the fimbrial end of the fallopian tubes, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The presumed precursor tubal lesion, localized at the fimbrial end of the fallopian tubes, is termed the serous tubal intraepithelial carcinoma. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presumed precursor tubal lesion, localized at the fimbrial end of the fallopian tubes, is termed the serous tubal intraepithelial carcinoma. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Other gynecological boards already declared the beneficial impact of PBS, however, no clear statement that PBS should be performed. [ 8 ] This critical review aims to study the risk-reducing potencies of PBS for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…More than 70% cases of patients with ovarian cancer are diagnosed in an advanced stage (FIGO stage III or IV) owing to nonspecific symptoms in the early stage and because of the lack of effective screening methods 2 . The mortality rate among EOC patients remains high and the 5-year overall survival (OS) is only 20%–40% for advanced disease, although some progress has been achieved in EOC treatment 3 . …”
Section: Introductionmentioning
confidence: 99%
“…Nonspecific symptoms in early stage of disease and a lack of effective screening methods are the main reasons why more than 70% of cases are diagnosed in FIGO stage Ⅲ or Ⅳ 2 . Despite the progress in therapy the mortality rate remains high with a five-year overall of only 20-40% for advanced disease 3 . Studies reported that approximately 95% of ovarian cancers are of epithelial origin and the high-grade serous caner (HGSC) represents 75% of EOC and accounts for the majority of deaths 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, removal of the fallopian tubes at the time of pelvic or abdominal surgery for a benign condition (i.e. opportunistic salpingectomy) appeared as an attractive option for primary prevention of HGSC 3 , 11 .…”
Section: Introductionmentioning
confidence: 99%